Differential expression of TGFβ isoforms in breast cancer highlights different roles during breast cancer progression - Mahmood Y Hachim; Ibrahim Y Hachim; Meiou Dai; Suhad Ali; Jean-Jacques Lebrun (Tumor Biology)
While TGFβ plays a critical role in tumor formation and progression, the role and contribution of its three different isoforms remain unclear. In this study, we aimed at elucidating the prognostic value of the TGFβ isoforms and assessed their expression levels in breast cancer patients at different stages of the disease. We found higher levels of TGFβ1 and TGFβ3 in cancer patients compared to normal tissues, with no significant changes in TGFβ2 expression. Similarly, TGFβ1 and TGFβ3, but not TGFβ2, showed higher expression levels in advanced lymph node–positive and metastatic tumors, suggesting different roles for the different isoforms in tumor progression and the metastatic process, while in the least aggressive molecular subtype (luminal A), expression of the three TGFβ isoforms significantly correlated with expression of both TGFβ receptors, such correlation only occurred between TGFβ1 and TGFβ3 and the TGFβ type II receptor (TβRII) in the highly aggressive basal-like subtype. Interestingly, a distinct and somehow opposite pattern was observed in HER-2 tumors, only showing significant association pattern between TGFβ2 and the TGFβ type I receptor (TβRI). Finally, the three TGFβ isoforms showed distinct association patterns with patient outcome depending on the different molecular subtype, highlighting context-dependent, differential prognostic values.